An experimental analysis of the performance of direct absorption parabolic trough collectors with laser-processed copper surfaces - Amirhossein Edalatpour; S. M. Hosseinalipour; Mahdi Moghimi (Scientific Reports)
Abstract The growing demand for renewable energy sources has made solar energy an ideal choice due to its unlimited and readily available nature. Direct and indirect absorption parabolic solar collectors are widely used to harness solar energy for water heating in laboratory and industrial applications. In this research, modifications were made to the absorber tube to enhance the efficiency of a Direct Absorption Parabolic Trough Collector (DAPTC). Fiber laser processing is applied to copper surfaces placed at the center of the absorber tube. The spectroscopy technique was used to analyze the main laser parameters, including frequency, speed, and power. It was determined that applying a laser with a frequency of 20 kHz, a speed of 20 mm/s, and 80% of the power of a 30 W laser machine significantly reduces surface reflection. Various patterns, including horizontal lines, vertical lines, and circle patterns, were engraved on the surfaces to evaluate their impact on heat transfer and thermal efficiency improvement. The findings are presented based on an experimental approach, wherein a system was constructed to investigate these effects, and the relevant considerations are discussed. The results indicate that using an unprocessed copper surface increases the thermal efficiency of the collector by up to 32.83%. When laser-processed surfaces with different patterns are used, this increase reaches up to 38.99%. The maximum pressure drop across these surfaces is reported to be 247 Pa, and the performance index ranges between 0.84 and 1.06, indicating the effective operation of the collector using these surfaces.